Deceiving the spirit: engaging with the Holy Spirit in Catholic Uganda - Ravalde, Liz (Africa, 2019)
During ethnographic fieldwork among lay Catholics in eastern Uganda, informants occasionally turned to deception in their dealings with God and the Holy Spirit; in doing so, they appeared to reject the Christian notion of divine omnipotence and omniscience. Based on ethnography conducted in a sub-county I call Buluya, this article tries to explain how such attempts are deemed possible and plausible. My argument is made up of two main strands. First, I argue that, in an indeterminate social landscape in which no one can ever fully 'know' (ngeo) another person, many interpersonal relationships in Buluya are firmly grounded in practical efforts to gain better jobs, more money, education and greater security. I show how deception is a normal and morally neutral aspect of these relationships, as each party strives to protect what they have, and to improve their prospects. Second, I draw on ethnographic and historical data to suggest that the Holy Spirit has entered into the local cosmology in Buluya as a powerful yet limited being, dependent to some extent on the guidance of its human mediators. Finally, I bring these two strands together to suggest that, when the Holy Spirit is conceived of as a limited being (it, too, does not fully know people), relationships with it that take place through a human mediator can also be legitimately characterized by deception, without risking the work of the Holy Spirit. (English)
Paid
Keywords: CATHOLIC Church; COSMOLOGY; ETHNOLOGY; HOLY Spirit; OMNISCIENCE (Theory of knowledge)